ANALISIS BIAYA DAN INDEKS UTILITAS YANG DIUKUR MENGGUNAKAN SF-6D PADA PASIEN GAGAL GINJAL KRONIS DENGAN HEMODIALISIS DI RSUD ADJI BATARA AGUNG DEWA SAKTI KUTAI KARTANEGARA - Abdul Mahmud Yumassik; Gunawan Pamudji Widodo; Tri Murti Andayani (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Hemodialysis (HD) patients with chronic kidney disease takes a long time and requires patient compliance. This will give the patient a psychological stressor which will then affect the quality of life. Apart from having an effect on quality of life, therapy hemodialysis also used a high cost, especially if the patient has complications. The purpose of this study was to determine the amount of hemodialysis costs, utility index, and the effect of complications on costs and utility index in hemodialysis patients. This study was a cross-sectional analytical research with the perspective of hospital. The research subjects were outpatient CKD who underwent hemodialysis at the HD Unit of Adji Batara Agung Dewa Sakti Hospital in September-Oktober 2020. Data were obtained use the SF-6D instrument, medical records, and financial financing. Data analysis used independent sample t-test and Kruskal-Wallis.The results showed that the average real cost of therapy in hemodialysis patients for a month was Rp. 12,014,488±0, while the real cost per hemodialysis episode is Rp. 1,316,722±273,989. The mean value of patient utility index as measured by the SF-6D was 0.717±0.143. The statistical test results show a significant value of 0.049 <0.05 on the utility index, which means that there is a relationship between complications on the utility index and a significant value of 0.125> 0.05 on costs, which means that there is no relationship between complications and costs in CKD patients with hemodialysis Keywords: Hemodialysis, Cost analysis, Index utility, SF-6D